Efficient Electrocatalytic Reduction of CO2 by Nitrogen‐Doped Nanoporous Carbon/Carbon Nanotube Membranes: A Step Towards the Electrochemical CO2 Refinery. (1st June 2017) - Wang, Hong; Jia, Jia; Song, Pengfei; Wang, Qiang; Li, Debao; Min, Shixiong; Qian, Chenxi; Wang, Lu; Li, Young Feng; Ma, Chun; Wu, Tom; Yuan, Jiayin; et al.
Abstract: Herein we introduce a straightforward, low cost, scalable, and technologically relevant method to manufacture an all‐carbon, electroactive, nitrogen‐doped nanoporous‐carbon/carbon‐nanotube composite membrane, dubbed "HNCM/CNT". The membrane is demonstrated to function as a binder‐free, high‐performance gas diffusion electrode for the electrocatalytic reduction of CO2 to formate. The Faradaic efficiency (FE) for the production of formate is 81 %. Furthermore, the robust structural and electrochemical properties of the membrane endow it with excellent long‐term stability.